2017
DOI: 10.1039/c7cc02988h
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular delivery of a catalytic organometallic complex

Abstract: We show the intracellular delivery of a homogeneous palladium–peptide catalyst able to bioorthogonally activate a profluorophore inside living prostate cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…The directness of the thioether propargyl motif for palladium binding, the non-toxicity of palladium catalysts and facile synthetic access to bifunctional conjugates makes this a useful strategy for controlled metal mediated small molecule activation. Although we have demonstrated that the reaction rate is suitable for drug activation on cells, for in vivo applications the development of new palladium compounds is still needed to circumvent the lack of cell selectivity of the catalyst and the toxicity of the metal when used in non-complexed 30 or nanoparticle-functionalised form. 31 We are also exploring extensions of this strategy by using non-internalizing antibodies to allow exclusive extracellular decaging within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The directness of the thioether propargyl motif for palladium binding, the non-toxicity of palladium catalysts and facile synthetic access to bifunctional conjugates makes this a useful strategy for controlled metal mediated small molecule activation. Although we have demonstrated that the reaction rate is suitable for drug activation on cells, for in vivo applications the development of new palladium compounds is still needed to circumvent the lack of cell selectivity of the catalyst and the toxicity of the metal when used in non-complexed 30 or nanoparticle-functionalised form. 31 We are also exploring extensions of this strategy by using non-internalizing antibodies to allow exclusive extracellular decaging within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…After prodrug administration, these organometallic devices serve to produce the active drugs locally, which can have beneficial therapeutic effect . For intracellular applications, the metal catalyst can be fused to e. g. cell‐penetrating peptides …”
Section: Figurementioning
confidence: 99%
“…The following enzymes were rescued by allenyl-removal through Pd3-Pd6 in HEK293T cells: Taq DNA polymerase, Src kinase and the anthrax lethal factor endopeptidase [48]. Recently, cell-penetrating peptides were linked to a Pd-complex Pd7 (Table 2, entry 13), improving its internalization (Table 2, entry 13) [49]. The uncaging of poc-R110 in prostate adenocarcinoma (PC-3) cells was demonstrated [49].…”
Section: Homogeneous Palladium Catalystsmentioning
confidence: 99%
“…Recently, cell-penetrating peptides were linked to a Pd-complex Pd7 (Table 2, entry 13), improving its internalization (Table 2, entry 13) [49]. The uncaging of poc-R110 in prostate adenocarcinoma (PC-3) cells was demonstrated [49]. The peptide-based platform facilitates the delivery of metal-complexes to specific cell-types, thus opening the possibility of targeted drug delivery [50,51].…”
Section: Homogeneous Palladium Catalystsmentioning
confidence: 99%